Pengaruh Penambahan Molases Pada Kulit Pisang Kapendis Untuk Media Produksi Xilanase B.Stearothermophillus DSM 22 - -, Trismillah (Jurnal Sains dan Teknologi Indonesia, 2013)
Cavendish banana peel can be used as a substitute for the expensive xylan, while molasses than as a source of carbon as well as nitrogen, minerals and nutrients needed for the growth of microbes that can produce the enzyme. Xylanase produced from Bacillus stearothermopillus DSM 22, using media cavendish banana peels with the addition of molasses 1%, 2%, and 3%. Fermentation is done in a shaker incubator at 550C temperature conditions, initial pH 8, and 250 rpm agitation. The result showed the highest enzyme activity of 4,14 ± 0,16 U/mL min., on the addition 2% molasses after 24 hours. Further fermentation carried out in the fermenter working volume of 3.5 liters, with the condition of temperature 550C, pH 8, aeration 1 vvm, agitation 250 rpm, the highest spesific enzyme of activity of 51,62 ± 0,16 U/mg after 24 hours. Partial purification of xylanase enzyme fermentation is done with the results of microfiltration, ultrafiltration, ammonium sulfate (0-80%) and dialysis. There is an increase in the purity of the enzyme at each stage of purification, the highest purity on dialysis 3.23 times of crude enzymes.Kulit buah pisang kapendis dapat digunakan sebagai pengganti xilan yang harganya mahal, sementara molases selain sebagai sumber karbon serta nitrogen, mineral dan nutrisi dibutuhkan untuk pertumbuhan mikroba yang dapat menghasilkan enzim. Xilanase yang dihasilkan dari Bacillus stearothermopillus DSM 22, menggunakan media kulit pisang kapendis dengan penambahan molase 1%, 2%, dan 3%. Fermentasi dilakukan dalam shaker inkubator pada temperatur 550C, pH awal 8, dan agitasi 250 rpm. Hasilnya menunjukkan aktivitas enzim tertinggi 4,14 ± 0,16 U/mL min., pada penambahan 2% molases setelah 24 jam. Selanjutnya fermentasi dilakukan di dalam fermentor, volume kerja dari 3,5 liter, dengan kondisi temperatur 550C, pH 8, aeration 1 vvm, agitasi 250 rpm, aktivitas spesifik tertinggi 51,62 ± 0,16 U/mg setelah 24 jam. Pemurnian parsial fermentasi enzim xilanase dilakukan dengan hasil mikrofiltrasi, ultrafiltrasi, amonium sulfat (0-80%) dan dialisis. Ada peningkatan kemurnian enzim pada setiap tahap pemurnian, kemurnian tertinggi pada dialisis 3,23 kali dari enzim kasar.Keywords: Xylanase, B. stearothermophillus DSM 22, Cavendish banana peel, molasses, enzyme activity